Relationship between Internal Branding and Employee Performance in Private College Central (PCC) Regions of Malaysia: A Preliminary Review - Edward, Edmund (International Journal of Scientific Research and Management (IJSRM), 2023)
The idea of internal branding is becoming more and more common for coordinating employee behaviour or performance. However, as prior studies primarily examined the relationship between internal branding practices and employee performance within other industries, there is still a dearth of study in Malaysia pertaining to private tertiary institutions. Therefore, the goal of this study is to examine the variables that affect employee performance among Malaysian employees of Peninsula College Central (PCC). This study concentrated on the relationship between internal branding strategies and employee performance, particularly as it relates to knowledge, reward, and leadership. Social Exchange Theory served as the foundation for this study. The connection between employee-employer reciprocity and this notion is well established. The population in this study was 100 with a sample size of 80 employees of PCC. The researcher focused on the quantitative approach. Probability sampling was employed, and simple random sampling suits the probability sampling methods for a sample in PCC. Version 24 Statistical Package for the Social Sciences (SPSS) was applied to analyse the study. The results of this study indicate that the knowledge and reward have a significant effect on employee performance.